100 gradusov po Tsel'siiu . 100 gradusov po Tsel'siiu . 100 Degrees Celsius . 100 градусов по Цельсию - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. The life of soldiers in disciplinary battalions; the history of the missing Russian "imperial" gold; the bunker in Sverdlovsk; transsexuals. Featured in the program: Zhirinovskii, Vladimir Vol'fovich (Chairman of the Liberal Democratic Party faction) Contributors: Sychev, Dmitrii (Anchor) Жизнь солдат в дисциплинарных батальонах; история пропажи российского "царского" золота; о бункере в Свердловске; о транссексуалах. В программе участвуют: Жириновский, Владимир Вольфович (Председатель фракции ЛДПР) Создатели: Сычев, Дмитрий (Ведущий/Ведущая)